Parents’ sports-related behaviors, self-concept of ability, interest and organized after-school sports activities participation among Chinese elementary school children - Jiang, Chuantong; Razak, Norsilawati Abdul; Rasyid, Nelfianty Mohd; Cheng, Hui (Frontiers in Psychology, 2025)
BackgroundGrounded in Expectancy-Value Theory, this study investigated how parents’ sports-related socialization behaviors in the family context influence their children’s participation in organized after-school sports activities. More precisely, the research analyzed the mediating effect of self-concept of ability and interest in the relationship between parents’ sports-related socialization behaviors and children’s participation in organized after-school sports activities.MethodsThe research sample was derived from elementary schoolchildren in the 5th and 6th grades in urban areas of Zhaoqing, China. A total of 367 participants completed the questionnaire (177 boys; 190 girls; Mage = 11.17 years; SD = 0.663; age range = 10–12 years). The collected data were then utilized for further structural equation modeling (SEM) analysis.ResultsThe results indicated that parents’ sports-related socialization behaviors had significant direct and indirect effects on children’s participation in organized after-school sports activities. Specifically, the self-concept of ability and interest mediated the relationship between parental behaviors and children’s sports activities participation, respectively. Also, the self-concept of ability and interest serially mediated the relationship between parental behaviors and children’s sports activities participation.ConclusionThese findings underscore the crucial role parents play in their children’s participation in organized after-school sports activities. The study implies that initiatives should be taken to guide parents to perform positive family-supportive behaviors, such as offering encouragement, participating in co-activities, providing activity-related materials, and acting as role models. These behaviors can not only directly contribute to children’s participation in after-school sports activities but also indirectly influence it by enhancing children’s self-concept of sports ability and cultivating their interest in sports activities.